Integrated crop management for off-season capsicum production - Singh, S S; Mer, Rakesh; Renu; Nainwal, Mukta (Indian Horticulture, 2023)
Field demonstrations were carried out in selected villages of Almora district in Uttarakhand during 2020 and 2021 in off-season capsicum. Three components namely, varietal introduction, nutrient management and pest and disease management have been demonstrated with farmers participatory approach. A total of 120 demonstrations were conducted in 5 ha area during both the years. The demonstration of Indra hybrid under proper nutrient, pest and disease management gave 13.5 metric tonnes/ha productivity as compared to 7.75 metric tonnes/ha productivity recorded on farmers field. The net income received in the demonstrations was also higher. The article discusses the ICM strategies adopted to enhance the off-season capsicum production.